Functional Genetic Polymorphisms in the IL1RL1–IL18R1 Region Confer Risk for Ocular Behçet’s Disease in a Chinese Han Population - Tan, Xiao; Zhou, Qingyun; Lv, Meng; Tan, Handan; Wang, Qingfeng; Zhang, Liming; Cao, Qingfeng; Yuan, Gangxiang; Su, Guannan; Kijlstra, Aize; Yang, Peizeng (Frontiers in Genetics, 2020)
Single nucleotide polymorphisms (SNPs) in the IL1RL1-IL18R1 region are associated with various immune-mediated diseases. This study was carried out to investigate the causal variant for ocular Behcet’s disease and elucidate its target genes in the IL1RL1-IL18R1 region. Nine candidate functional SNPs were prioritized with bioinformatic analysis, followed by a two-stage association study in 694 ocular BD patients and 1458 unaffected controls. Functional studies were performed in PBMCs of 45 healthy men and 16 active male BD patients. Genotyping was performed using the MassARRAY System. The mRNA expression of IL1RL1, IL18R1, IL18RAP and SLC9A4 were assayed by real-time PCR and secretion of cytokines was examined by ELISA. A significant lower frequency of the rs12987977 GG genotype/G allele (Pc=2.68×10−6, OR=0.39; Pc=5.20×10−3, OR=0.77, respectively), rs12999364 TT genotype/T allele (Pc=9.45×10−4, OR=0.51; Pc=2.25×10−2, OR=0.80, respectively), and rs4851569 AA genotype/A allele (Pc=9.86×10−4, OR=0.52; Pc=1.94×10−2, OR=0.80, respectively) was observed in BD patients compared with controls. Functional experiments revealed a downregulation of IL1RL1, IL18R1, SLC9A4 and a decreased secretion of IFN-γ in anti-CD3/CD28 antibody-treated PBMCs as well as a decreased production of TNF-α in LPS-stimulated PBMCs in carriers of the protective homozygous rs12987977/GG genotype compared with TT genotype. Our findings show that functional SNPs—rs12987977, rs12999364 and rs4851569 in the IL1RL1-IL18R1 region confer susceptibility to ocular BD in a Chinese Han population. And IL1RL1, IL18R1 and SLC9A4 may be the target genes of rs12987977.